2019
DOI: 10.21037/jtd.2019.10.77
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function is implicated in the prognosis of metastatic non-small cell lung cancer but not in extended disease small cell lung cancer

Abstract: Background: The impacts of pulmonary function in patients with metastatic non-small cell lung cancer (NSCLC) and extended disease stage small cell lung cancer (SCLC-ED) treated with palliative chemotherapy remain to still be determined. Methods: Results of spirometry performed in 449 patients with either stage IV NSCLC (n=313) or SCLC-ED (n=136) at diagnosis were reviewed retrospectively. Overall survival (OS) was estimated using the Kaplan-Meier method and compared via a log-rank test. Multivariate analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Numerous studies have focused mainly on the prognostic value of preoperative pulmonary function in lung cancer but rarely in digestive cancers. These studies have clearly shown that preoperative pulmonary evaluation could be used as a predictor for postoperative complications and survival in lung cancer[ 9 , 23 ]. As described previously, FVC and VC have been demonstrated as predictors of postoperative complications and the survival in gastric cancer[ 10 ] and Japanese esophageal cancer[ 11 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have focused mainly on the prognostic value of preoperative pulmonary function in lung cancer but rarely in digestive cancers. These studies have clearly shown that preoperative pulmonary evaluation could be used as a predictor for postoperative complications and survival in lung cancer[ 9 , 23 ]. As described previously, FVC and VC have been demonstrated as predictors of postoperative complications and the survival in gastric cancer[ 10 ] and Japanese esophageal cancer[ 11 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that poor pulmonary function is associated with severe postoperative complications in patients undergoing esophagectomy[ 4 - 6 ]. Some studies have reported that reduced pulmonary function is associated with mortality risk in the general population[ 7 , 8 ], lung cancer[ 9 ] and gastric cancer[ 10 ], while little attention has been given to the correlation between preoperative pulmonary evaluation and the overall survival of esophageal cancer patients. Forced vital capacity (FVC) and vital capacity (VC) are both important parameters in pulmonary evaluation test.…”
Section: Introductionmentioning
confidence: 99%
“…This inconsistence can be attributed to the heterogeneity of the study population. 7 , 36 The lung cancer stage, pathology, and treatment of patients differ in each study; therefore, the effects of COPD may differ in studies with different populations. A number of studies have previously reported that COPD has a greater impact on early‐stage lung cancer than on advanced‐stage lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in advanced NSCLC, several studies have reported that forced expiratory volume in 1 second (FEV 1 ) less than 50% predicted or the presence of COPD were associated with mortality [11][12][13]. Because severity of air ow obstruction and acute exacerbations are predictors of mortality in COPD patients [14][15][16], improving these factors might also be important in patients with advanced NSCLC and COPD.…”
Section: Introductionmentioning
confidence: 99%